Efficacy and aesthetic outcomes for quilting sutures in the prevention of seroma after mastectomy - Arthur Foulon; Albine Mancaux; Pierrick Theret; Philippe Naepels; Johanna Mychaluk; Philippe Merviel; Pascal Abboud; Raffaele Fauvet (Scientific Reports, 2023)
Abstract Worldwide, mastectomy for breast cancer is one of the most frequently performed surgical procedures. As one of the main complications of mastectomy, seroma is associated with pain, infections and a prolonged hospital stay. We performed a prospective multicenter randomized trial to assess the efficacy and esthetic outcomes associated with quilting the skin flap. Eighty-seven patients were included. The proportion of patients with seroma on postoperative day 15 was significantly lower in the quilting group (12 out of 39 (30.8%)) than in a control group with conventional wound closure (21 out of 40 (52.5%); P = 0.05). The mean breast seroma volume was significantly lower in the quilting group (130.2 mL) than in the control group (236.8 mL; P = 0.02). There were no differences in the esthetic outcomes. The pain level on day 1 was similar in the quilting and control groups (mean visual analog scale score: 2.5 vs. 2.1, respectively; P = 0.3). Quilting the skin flap was associated with a lower prevalence of seroma and a lower seroma volume, and did not worsen the esthetic outcomes or pain levels. This technique is technically straightforward and should be offered to all patients scheduled for mastectomy.